Prevalence of Text Neck Syndrome Among Physiotherapy Students in Visakhapatnam: Cross-Sectional Study - Palanigounder, Raju; Raju, Karthikeyan (Journal of Social Science and Humanities, 2025)
Background: Smartphones are among the most widely used electronic devices, leading to prolonged neck flexion and increasing the risk of text neck syndrome. Aim of the study: This study aims to assess the prevalence of text neck syndrome and smartphone addiction among physiotherapy students in Visakhapatnam. Methodology: A cross - sectional study was conducted over six months with a sample of 250 students using a random sampling technique. Data were collected using a self - administered questionnaire, including demographic details, the Smartphone Addiction Scale - Short Version (SAS - SV), and the Neck Disability Index (NDI). Results: The results indicated that 63.59% of students exhibited symptoms of text neck syndrome, with 49.51% reporting mild neck disability. Additionally, 61.65% of students demonstrated significant smartphone addiction. Conclusion: A moderate positive correlation was observed between smartphone addiction and neck disability. The study highlights the increasing risk of text neck syndrome among young adults and emphasizes the need for preventive measures.